2010
DOI: 10.1121/1.3455795
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of ultrasound scattering from individual micron-sized objects and its application in single cell scattering

Abstract: The measurement of the ultrasound backscatter from individual micron-sized objects such as cells is required for various applications such as tissue characterization. However, performing such a measurement remains a challenge. For example, the presence of air bubbles in a suspension of cells during the measurements may lead to the incorrect interpretation of the acoustic signals. This work introduces a technique for measuring the ultrasound backscatter from individual micron-sized objects by combining a microi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 25 publications
3
25
1
Order By: Relevance
“…20 It was found that the BSC from an isolated cell was best modeled as a fluid sphere having the whole cell size. 23 Taggart et al 24 conducted high frequency ultrasound measurements on cell pellets (i.e., highly packed cells) made up of mono-and multi-nucleated cells or isolated nuclei. This study suggests that the integrated BSCs were correlated with the size of the nuclei.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 It was found that the BSC from an isolated cell was best modeled as a fluid sphere having the whole cell size. 23 Taggart et al 24 conducted high frequency ultrasound measurements on cell pellets (i.e., highly packed cells) made up of mono-and multi-nucleated cells or isolated nuclei. This study suggests that the integrated BSCs were correlated with the size of the nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the scattering sites will lead to the improvement of the theoretical scattering models. Baddour et al 21,22 and Falou et al 23 performed measurements of high frequency MHz) ultrasound BSC responses from individual cells and modeled a cell as a single spherical scatterer with uniform acoustic properties. The BSC measurements were compared to theoretical BSC predictions from a fluid sphere model 9 or from an elastic sphere model.…”
Section: Introductionmentioning
confidence: 99%
“…Falou et al . reported theoretical and experimental backscattering results on elastic and fluid spheres from a micrometer-sized polystyrene object and single OCI-AML-5 cell at 25 and 55 MHz, and these results showed that backscattering from a single OCI-AML-5 cell can be modeled as an elastic and a fluid sphere [13]. The results showed a good agreement between theoretical and experimental results.…”
Section: Introductionmentioning
confidence: 83%
“…Currently there is no consensus on the dominant ultrasonic scattering source of biological structures. Some studies support the hypothesis that the whole cell acts as a dominant scatterer source (Falou et al 2010;Oelze and Zachary 2006). Other studies suggest that the nucleus is the main scatterer source when cells are embedded in tumors or surrounded by other cells (Czarnota et al 1999;Kolios et al 2003;Taggart et al 2007).…”
Section: Introductionmentioning
confidence: 92%